CHANGE AND CONTINUITY IN A POLITICAL-ECONOMIC CONTEXT IN TURKEY: THE RISE OF ECONOMIC POWER OF RELIGIOUS SEGMENTS - Özoral, Başak (European Scientific Journal, ESJ, 2014)
In recent years, much of the discussion about the Turkey has focused on the increasing role of Islam in politics and economics. In contemporary Turkey, previously rejected values have begun to be absorbed by different segments of the society. For example, the variance between Western concepts such as liberalism and modernity and their interpretation by Islamists has resulted in a search for such values in Islam and in the struggle to prove the compatibility of Islam and democracy. With the result of that Islamic values and ethics and modernity are no longer viewed as ideologically incompatible. This new paradigm that accepts liberalism and modernity as being compatible with Islam has been observed in different Islamist groups, in varying degrees. This paper will focus on one of the chief actors which played crucial roles in the above mentioned socio-economic transformation in Turkey, namely: the economic organization MÜSİAD (Independent Industrialists’ and Businessmen’s Association). The purpose of this study here is to elaborate on the degree of change in their discourse. Actually, this paper points out that the integration of pious Muslim businessmen in modern global market now tends to be self-referring, instead of it being defined as opposed to traditionalism.